Voices of influence: mastering persuasive speaking skills. a comprehensive teaching module for ESP/ ESL/ EFL speakers - Abdul Latif @ Bapoo, Lilisuriani; Mohd Noor Be, Nur Iylia; Idrus, Azean Idruwani (KSTCL Press, 2025)
Empower your learners or trainees to speak with purpose, confidence, and impact. This master module is a comprehensive teaching resource designed specifically for ESP, ESL, EFL educators or in-house trainers who want to elevate learners’ communicative competence through real-world persuasive speaking strategies. Blending rhetorical theories and practical frameworks with English language phrases, sociolinguistic awareness, Islamic values, and global themes like the SDGs, this resource equips language and communication instructors with ready-to-use ideas and lessons that provide engaging activities. Whether you're preparing students for academic proposals, professional pitches, or team persuasive presentations, this master module allows you to choose and customize your course content and provides the tools to teach persuasive speaking with clarity, ethics, and relevance.